FAKTOR-FAKTOR YANG MEMENGARUHI PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR - Jonathan Jonathan; Yohanes Yohanes (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2022)
The purpose of this study was to examine the effect of profitability, leverage, firm size, capital intensity, sales growth, and audit quality on tax avoidance. Previous researchers used 4 variables, namely profitability, leverage, firm size, and capital intensity. This study adds the variables of sales growth and audit quality. This study uses manufacturing companies listed on the Indonesia Stock Exchange during 2016 to 2018 as the population. There are 70 companies as a sample that meet the criteria by using purposive sampling method. This research model uses multiple regression analysis. The results of this study indicate that profitability and sales growth have an effect on tax avoidance, while other independent variables such as leverage, firm size, capital intensity and audit quality have no effect on tax avoidance. The higher the sales growth, the higher the tax avoidance practice. The greater the profitability of the company, the policy to carry out tax avoidance practices will decrease because the company is able to pay corporate taxes and the higher the practice of tax avoidance. This is because companies that have relatively large sales levels will provide opportunities to earn large profits as well. This is because companies that have relatively large sales levels will provide opportunities to earn large profits as well. Keywords: Profitability, leverage, firm size, capital intensity, sales growth